(untitled) (Research, Society and Development, 2023)
The meninges are connective tissue structures that surround the central nervous system (CNS) and their functions include mechanical protection and formation of the blood-brain barrier. In turn, meningiomas are CNS tumors, mostly benign, which originate from non-epithelial precursor cells of the meninges. The aim of this paper is to describe an uncommon case in the medical literature: the incidence of metastasis from a grade II cranial meningioma to a lymph node in the cervical chain. Thus, we report the case of an elderly man who underwent a computed tomography of the skull after a mild domestic incident, which showed the existence of an intracranial tumor, the patient being asymptomatic. From then on, the investigation began, leading to the diagnosis of post-biopsy meningioma. Months later, an abnormal bulge in the cervical region was observed, leading to a new investigation and a new diagnosis: grade II meningioma associated with lymph node metastasis. The surgical approach seems to be preferred in progressively growing, recurrent and symptomatic meningiomas; the association with biological therapies, such as somatostatin analogues, can delay its growth.